133k views
3 votes
If f(x)=-5x-4 and g(x)=-3x-2 find (f+g)(x)

User MKane
by
6.3k points

2 Answers

5 votes

Sure! If you have two functions, \(f(x)\) and \(g(x)\), and you want to find the sum of these functions, denoted as \((f+g)(x)\), you simply add the two functions together.

Given that:
\[f(x) = -5x - 4\]
\[g(x) = -3x - 2\]

You can find \((f+g)(x)\) by adding \(f(x)\) and \(g(x)\) together, like so:

\[(f+g)(x) = f(x) + g(x)\]

Now, we substitute the given functions into the equation:

\[(f+g)(x) = (-5x - 4) + (-3x - 2)\]

Combine like terms (the terms with \(x\) and the constant terms):

\[(f+g)(x) = -5x - 3x - 4 - 2\]

Combine the x terms:

\[ = (-5 - 3)x + (-4 - 2)\]
\[ = -8x + (-6)\]
\[ = -8x - 6\]

Therefore, the sum of the functions \(f(x)\) and \(g(x)\), or \((f+g)(x)\), is:

\[(f+g)(x) = -8x - 6\]

User ShermanL
by
6.0k points
4 votes

Answer:

(f + g)(x) = -5x -3x - 6

Explanation:

Given: f(x)=-5x-4 and g(x)=-3x-2

(f + g)(x) = f(x) + g(x)

Now plug in the given expressions f(x)=-5x-4 and g(x)=-3x-2, we get

(f + g)(x) = -5x -4 + (-3x -2)

Now we distribute the + sign inside the parenthesis, we get

(f + g)(x) = -5x - 4 - 3x - 2

Now we can add -4 and -2, which is -6

(f + g)(x) = -5x -3x - 6

We can also add the like terms -5x - 3x

Since it was not given in your option.

So the answer is -5x -3x - 6

User Hassan Jalil
by
6.2k points